Poverty Reduction Support Credits : Mozambique Country Study - Horton, Brendan (Washington, DC: World Bank, 2017)
Mozambique acquired independence from Portugal in 1975. The new government adopted a policy of radical social change, with a command and control approach to economic management and a vast nationalization program. By the mid-1980s, the country was bankrupt, and the government turned to the International Monetary Fund (IMF) and the World Bank to help transform it into a market economy. Since the early 1990s, Mozambique's Gross Domestic Product (GDP) growth rate has been above 7 percent in all but two years and has averaged 7.8 percent. Over the same period, inflation has trended broadly downwards from 63 percent in 1994 to 8 percent in 2007. On the savings and investment front, gross investment has averaged 26.4 percent, while domestic savings has been 8.2 percent, the difference being made up for with foreign savings. Fiscal policy has generally been well managed, with deficits financed by external assistance. The government managed to protect the 65 percent of primary expenditures going to priority sectors. Public investment declined as a percentage of GDP, as did private investment. Revenue collection improved. Exports grew from 10.2 percent of GDP in 1991 to 38 percent in 2006. Over this period, a flexible exchange rate policy has been followed. The national poverty rate was 69.4 percent in 1996-1997 and 54.1 percent in 2003. Mozambique obtained considerable fast disbursing assistance from the World Bank in the period 1984-2002.